2019
DOI: 10.1007/s12550-019-00381-9
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins in blood and urine of Swedish adolescents—possible associations to food intake and other background characteristics

Abstract: The exposure to mycotoxins of Swedish adolescents is currently unknown. The aim of the present study was to investigate the exposure to mycotoxins and their association with food intake, and background characteristics in adolescents of a national dietary survey. About 3000 school students (1000 from the 5th, 8th and 11th school years) were recruited for the survey. The participants completed Web-based questionnaires on food propensity, sociodemography and health, and a Web-based dietary recall. Spot urine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 55 publications
5
47
1
Order By: Relevance
“…Milk and dairy consumption was negatively correlated with the OTA levels ( r s = −0.275) but positively correlated with FB1 levels ( r s = 0.362). There were no statistically significant correlations ( p < 0.05) between mycotoxins exposure and food consumption except OTA and beverages such as coffee and tea, which was consistent with several previous studies [ 48 , 49 ] and might be caused by the heterogeneous distributions of mycotoxins in foodstuffs, various routes of mycotoxin exposure, and the inaccurate dietary intake in questionnaires [ 50 ].…”
Section: Resultssupporting
confidence: 90%
“…Milk and dairy consumption was negatively correlated with the OTA levels ( r s = −0.275) but positively correlated with FB1 levels ( r s = 0.362). There were no statistically significant correlations ( p < 0.05) between mycotoxins exposure and food consumption except OTA and beverages such as coffee and tea, which was consistent with several previous studies [ 48 , 49 ] and might be caused by the heterogeneous distributions of mycotoxins in foodstuffs, various routes of mycotoxin exposure, and the inaccurate dietary intake in questionnaires [ 50 ].…”
Section: Resultssupporting
confidence: 90%
“…De Santis et al (2017) [ 29 ] found levels of OTA at 82.9% in serum samples from 233 Italian children (aged 2–12 years); these authors also found other mycotoxins, but with a lower incidence: AFB1 (22.9%), AFM1 (50.2%), ZEA (5.4%), DON (19.5%), and DOM-1 (13.1%). Warensjö et al (2020) after studying the presence in the serum of 27 mycotoxins and related compounds, including AFs, DON, T-2, HT-2, OTA, and ZEA, among others, in more than 1000 school students in Sweden (11–18 years old) detected OTA in 100% of the serum samples, while among the other analyzed compounds, and apart from OTA, only 2’R-OTA and enniatin B were found [ 42 ]. Moreover, in the work of Erkekoǧlu et al (2010) [ 43 ], the incidence of serum OTA in children was 100%.…”
Section: Resultsmentioning
confidence: 99%
“…In which, Cp refers to the OTA plasma level (ng/mL); A refers to OTA bioavailability (believed to be 0.5); body weight (bw) (assumed to be 70 kg); and Cl renal is the daily renal clearance (mL/kg bw/day). For this last parameter, values of 0.048 mL/min or 0.1099 mL/min [47] have been proposed.…”
Section: Discussionmentioning
confidence: 99%